The Time Course of Activation of Semantic and Orthographic Information in Morphological Decomposition by Korean Adults and Developing Readers - Lin, Candise Y.; Wang, Min; Ko, In Yeong (Frontiers in Communication, 2018)
The current study examined the involvement of semantic and orthographic information in the processing of derived words in Korean Hangul. Sixth grade children and adults participated in four masked priming lexical decision experiments in which the prime duration varied from 36, 48, 57, and 72ms (in Experiments, 1, 2, 3, and 4, respectively). Morphological (M), semantic (S), and orthographic (O) relatedness between prime-target pairs were manipulated. There were four types of Korean prime-target pairs: (1) -M-S+O: 도시락-도시, scandal-scan, (2) +M-S+O: 구두쇠-구두, archer-arch, (3) +M+S+O: 음악가-음악, bravely-brave, and (4) -M+S-O: 반대-이의, accuse-blame. There were several key findings: (1) adults showed significant priming effects at 57 and 72ms in +M+S+O and significant priming effects at 72 ms in +M-S+O; (2) less skilled readers showed significant facilitation at 36ms in +M+S+O; and (3) in -M-S+O, both skilled and less skilled readers show significant inhibition across four prime durations. The different time course of +M+S+O priming for adults and children may be due to developing readers’ smaller lexicon and less competition for semantic activation of the monosyllabic suffix (e.g., 가 in 음악가), which is a homograph in Korean Hangul. The consistent orthographic inhibition for both age groups suggest that orthographic information is activated early and continues to play an important role throughout the course of Korean visual word recognition. The current study extends previous research with readers of Roman alphabets to readers of an alpha-syllabary orthography written in a nonlinear spatial layout with more clear-cut syllable boundaries. Taken together, it appears that the involvement of semantic and orthographic information in the decomposition of morphologically complex word may vary depending on the characteristics of the orthography.